Pemanfaatan dan Nilai Ekonomi Hasil Hutan Bukan Kayu di Wilayah Kerja Kesatuan Pengelolaan Hutan Kulawi (Studi Kasus Desa Walatana Kecematan Dolo Selatan) - Angriyani, Silma; Umar, Syukur; Pribadi, Hendra; Maiwa, Arman (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
Effective and sustainable management of Non-Timber Forest Products (NTFPs) plays an important role in supporting the local economy, reducing pressure on primary forests, and maintaining biodiversity. This research aims to determine the use of NTFPs and the economic value of NTFPs in Walatana Village, South Dolo District. The research was carried out by applying survey methods to respondents and observations, using an analytical approach to the use of Non-Timber Forest Products (NTFPs) resources. Respondents are residents of Walatanana Village who have interactions with forest resources. The general problem faced in this research is the lack of understanding and awareness of the community regarding the potential of Non-Timber Forest Products (NTFPs) in Walatana Village, South Dolo District. The research results show that the people of Walatana Village have utilized various types of NTFPs, including rattan, candlenuts, bamboo, honey and firewood. With the economic value of NTFPs reaching Rp. 515,484,000,- per year, of which rattan contributes Rp. 220,200,000,-, this research highlights the great potential of NTFPs in supporting the local economy. These findings emphasize the importance of involving the community in efforts to sustainably manage NTFPs, while increasing their understanding of the economic potential that can be generated. This research indicates the need for an educational and participatory approach to increase public awareness of the importance of NTFPs in the context of sustainability. This effort is expected to create a balance between the use of NTFPs as a source of income and maintaining the sustainability of forest ecosystems.